2005
DOI: 10.1583/05-1526.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Thromboembolic Events During Carotid Artery Angioplasty and Stenting:Etiology and a Technique of Neurorescue

Abstract: In our experience, intraprocedural thromboembolic events occur despite the use of cerebral protection devices, but are rare. Notably these complications appeared to occur at the time of lesion crossing by distal cerebral protection devices. These thromboembolic events can be successfully treated if the complication is rapidly identified and the physician is adequately prepared and proficient in neurorescue techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…These stents have considerably more bare metal surface area than coronary stents and have the potential for enhanced thrombogenicity. Several studies using diffusion‐weighted magnetic resonance imaging have shown a high incidence of micro‐emboli during CS, and acute carotid stent thrombosis, although rare, has been reported [20–23]. A direct thrombin inhibitor, such as bivalirudin, in conjunction with dual anti‐platelet blockade with aspirin and clopidogrel, may be important prophylaxis against thrombus formation during CAS.…”
Section: Discussionmentioning
confidence: 99%
“…These stents have considerably more bare metal surface area than coronary stents and have the potential for enhanced thrombogenicity. Several studies using diffusion‐weighted magnetic resonance imaging have shown a high incidence of micro‐emboli during CS, and acute carotid stent thrombosis, although rare, has been reported [20–23]. A direct thrombin inhibitor, such as bivalirudin, in conjunction with dual anti‐platelet blockade with aspirin and clopidogrel, may be important prophylaxis against thrombus formation during CAS.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 If a distal embolism develops, thrombolytic therapy with a recombinant tissue plasminogen activator or its analogue is theoretically ineffective because the embolus is comprised of plaque rather than thrombic material. 18 The effi cacy of infused platelet glycoprotein IIb/IIIa antagonist or abciximab, reported to be highly effective in thromboembolic events associated with neurointerventions, [19][20][21] may be limited to the prevention of secondary thrombus formation in the occluded vessel.…”
Section: Discussionmentioning
confidence: 99%
“…26 Embolism can occur both in CEA and in CAS. 27,28 Embolism related to the procedure can be assessed by transcranial Doppler sonography and cerebral MR imaging with DWI. However, there is no consensus regarding the true incidence and relevance of these events.…”
Section: Figmentioning
confidence: 99%